Transcriptional regulation in salmonids with emphasis on lipid metabolism - Schiller Vestergren, AnnaLotta (2014)
Fish is a vital source of valuable omega-3 (n-3) fatty acids (FA) in the human diet. With declining commercial fisheries, aquaculture fish constitute a growing proportion of human consumption. Sustainable development of aquaculture requires that the fish feed used is not solely based on fish meal and oil (FO), but also contains increasing levels of vegetable oil (VO). The replacement of FO with VO influences FA composition in fish tissues by decreasing n-3 long-chain polyunsaturated fatty acids (LCPUFAs) and the nutritional value for humans. Accordingly, the last decade of salmonid research has focused on increasing the amount of n-3 LCPUFAs in fish fed VO diets e.g. addition of bioactive compounds. This thesis examined the potential effects of bioactive compounds on lipid metabolism in salmonids. Genes involved in transcriptional regulation, uptake, β-oxidation, elongation and desaturation were shown to be affected by addition of bioactive compounds in both in vivo and in vitro experiments. Effects on FA composition were also observed, but no clear effect on docosahexaenoic acid (DHA) content. The discrepancies between increased gene expression of target genes in the desaturation and elongation cascade and the actual lack of response in FA content of eicosapentaenoic acid and docosahexaenoic acid may be the result of a combination of feedback regulation and post-transcriptional regulation, such as RNA silencing through microRNA (miRNA) repression. This thesis describes the miRNA transcriptome in liver tissue of Atlantic salmon post-smoltification and the tissue distribution of selected miRNAs in nine different somatic tissues of juvenile Atlantic salmon (Salmo salar) for the first time. The results expand the number of known Atlantic salmon miRNAs and provide a framework for understanding the n-3 LCPUFA pathway in Atlantic salmon.